2010
DOI: 10.4322/actalb.2011.003
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a waterfall over richness and similarity in adjoining pools of an Atlantic Rainforest stream

Abstract: Aim:The main goal of the study was to determine the effect of the Morato Fall in the richness and composition of the aquatic animal community; Methods: We compared faunal richness and similarity in four substrate samples from two pools separated by a waterfall in the Morato River, southern Brazil; Results: The richness was not significantly different, although the upstream pool had 72 taxa and the downstream one just 65. On the other hand, composition was poorly similar, just a 36.5% similarity between the two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…(Mendonça et al 2005, Espírito-Santo et al 2009, Dias et al 2010, Fernandes et al 2013, values similar to those reported here. Waterfalls are important barriers for aquatic organisms, preventing the movement and the exchange of species among regions (Rahel 2007, Jönck & Aranha 2010, Torrente-Vilara et al 2011. This study found a marked effect on the Dardanelos-Andorinhas waterfalls complex, which acted as natural barrier to fish species.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…(Mendonça et al 2005, Espírito-Santo et al 2009, Dias et al 2010, Fernandes et al 2013, values similar to those reported here. Waterfalls are important barriers for aquatic organisms, preventing the movement and the exchange of species among regions (Rahel 2007, Jönck & Aranha 2010, Torrente-Vilara et al 2011. This study found a marked effect on the Dardanelos-Andorinhas waterfalls complex, which acted as natural barrier to fish species.…”
Section: Discussionmentioning
confidence: 74%
“…The waterfalls act as natural ecological barriers limiting fish dispersal processes which causes significant differences in species composition between rivers stretches located upstream and downstream of the waterfall (Jönck & Aranha 2010, Torrente-Vilara et al 2011. Besides that, waterfall may affect genetic structure and increase genetic distance between local populations (Kano et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…& Garavello (2007), studying the Pâ ntano River and showing large varieties of species among the sites separated by Pântano waterfall, where only 13 species out of 63 were recorded. Also, Jonck & Aranha (2010) have studied the aquatic population of two pools, separated by a waterfall in a Atlantic Rainforest stream and have concluded that there is a strong influence of the obstacle, the waterfall, especially to the organisms that spend all their life cycle in water.…”
Section: Discussionmentioning
confidence: 99%